Rising from the Ashes of Cultural Devastation - Tabensky, Pedro (African studies (Johannesburg), 2025)
Following Jonathan Lear and Frantz Fanon, and disagreeing with both to some extent, I aim to make sense of what happens to a people when the conditions for their continued existence as those people have been radically and irreversibly eroded by colonial violence. I am also interested in understanding how and in what sense culture can be brought back to life once it has been crushed. Following Lear, I explore how Plenty Coups, the last great chief of the Crow nation, managed the transition of his people from hunter-gatherer warrior existence to reservation life. I think Lear's analysis of what he terms the 'ontological vulnerability' of all cultures helps explain what was at stake in this transition. However, I am not entirely satisfied with Lear's account of how the Crow could continue to be Crow once the conditions for traditional Crow existence are no longer present, but I owe him a debt of gratitude for helping me think through these complex issues. Fanon's account of culture and mutual recognition can help us better understand what is at stake. However, despite its richness, I am not wholly satisfied with the details of Fanon's project. I think his revolutionary psychiatry ultimately fails to achieve its emancipatory aims. I conclude by recommending a turn towards the poetic, something both Lear and Fanon recommend.